2020
DOI: 10.1136/jitc-2020-000807
|View full text |Cite
|
Sign up to set email alerts
|

Upfront dose-reduced chemotherapy synergizes with immunotherapy to optimize chemoimmunotherapy in squamous cell lung carcinoma

Abstract: BackgroundThe survival benefits of combining chemotherapy (at the maximum tolerated dose, MTD) with concurrent immunotherapy, collectively referred to as chemoimmunotherapy, for the treatment of squamous cell lung carcinoma (SQCLC) have been confirmed in recent clinical trials. Nevertheless, optimization of chemoimmunotherapy in order to enhance the efficacy of immune checkpoint inhibitors (ICIs) in SQCLC remains to be explored.MethodsCell lines, syngeneic immunocompetent mouse models, and patients’ peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…Additionally, increased understanding of the tumor microenvironment has led to the coupling of immunomodulatory therapies with chemotherapy ("chemoimmunotherapy") for the treatment of different cancers [41][42][43]. For example, squamous cell lung carcinoma represents up to 30% of all non-small cell lung cancers, yet treatment options are limited and mostly ineffective [44]. Squamous cell lung carcinoma tumors are more resistant to immunotherapy, and traditional chemotherapy treatments administered at the maximum tolerated dose are highly toxic to the patient with little effect on the tumor [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, increased understanding of the tumor microenvironment has led to the coupling of immunomodulatory therapies with chemotherapy ("chemoimmunotherapy") for the treatment of different cancers [41][42][43]. For example, squamous cell lung carcinoma represents up to 30% of all non-small cell lung cancers, yet treatment options are limited and mostly ineffective [44]. Squamous cell lung carcinoma tumors are more resistant to immunotherapy, and traditional chemotherapy treatments administered at the maximum tolerated dose are highly toxic to the patient with little effect on the tumor [44].…”
Section: Discussionmentioning
confidence: 99%
“…For example, squamous cell lung carcinoma represents up to 30% of all non-small cell lung cancers, yet treatment options are limited and mostly ineffective [44]. Squamous cell lung carcinoma tumors are more resistant to immunotherapy, and traditional chemotherapy treatments administered at the maximum tolerated dose are highly toxic to the patient with little effect on the tumor [44]. However, recent clinical trials have shown that coupling traditional chemotherapy with immunomodulatory therapy significantly increased patient survival [44].…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, therefore, the median duration of tumour responses with such combinations are not very different from those observed with chemotherapy alone in all of the registration trials 249 , 250 . Indeed, data from longer-term follow-up studies of those trials 251 , preclinical data 252 and case reports 253 suggest that systemic high-dose chemotherapies have a detrimental effect on the efficacy of anti-PD-1 and anti-PD-L1 antibodies, thus supporting the idea that metronomic chemotherapy might be a better way to exploit these immunomodulatory effects.…”
Section: Intratumoural Immunotherapiesmentioning
confidence: 99%
“…[10][11][12][13] Multiplex quantification of CD3 + and CD8 + T cells and flow cytometry analysis showed that PD-1 blockade favors tumor infiltration by CD8 + T cells, while in vivo CD8 + T cell depletion led to tumor growth restoration. 14,15 A previous report showed that chemotherapy could promote the differentiation of human T cells into Th1 and Th9 subtypes and cytotoxic T lymphocytes (CTLs) in vitro and in vivo. 16 As for TAMs, typically CD163-positive M2 macrophages, play an essential role in malignant tumor development, angiogenesis, lymphangiogenesis, and invasion as well as immune tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…High densities of CD3 + and CD8 + T cells have been shown to be associated with prolonged survival and significant therapeutic responses in cancer patients 10–13 . Multiplex quantification of CD3 + and CD8 + T cells and flow cytometry analysis showed that PD‐1 blockade favors tumor infiltration by CD8 + T cells, while in vivo CD8 + T cell depletion led to tumor growth restoration 14,15 . A previous report showed that chemotherapy could promote the differentiation of human T cells into Th1 and Th9 subtypes and cytotoxic T lymphocytes (CTLs) in vitro and in vivo 16…”
Section: Introductionmentioning
confidence: 99%